Using Critical Social Theory as Professional Learning to Develop Scholar—Practitioners in Physical Education: The Example of Bourdieu’s Theory of Practice - David H. K. Brown; Rhys G. Lloyd (Education Sciences, 2024)
In this conceptual article, we present the idea that the physical education (PE) teacher is, out of professional necessity, a scholar—practitioner. To substantiate and evolve this idea, we develop a Deweyian pragmatist view of the scholar—practitioner which also embraces criticality. This stance collapses the binary notion of theory and practice and instead embraces theory and practice as a duality. We add a critical dimension to this duality through recognising that scholar—practitioners (especially leaders) require criticality and cultural awareness to raise questions over knowledge conventions and the mitigations of contextual factors their learners may face. We then turn to the critical and practical sociology of Pierre Bourdieu to illustrate how the use of theory may help PE scholar—practitioners enhance their criticality and cultural awareness. More specifically, we draw on Bourdieu’s primary concepts of field, capital and habitus to show how the application of this theory can help PE scholar—practitioners position themselves in relation to their profession and how they might know their field; be aware of their, and their students’, capital worth in relation to that field; and know themselves (their personal—professional habitus). In conclusion, we suggest that for PE scholar—practitioners, theory-based learning and its applied use might be considered a form of professional learning and not be limited to Bourdieu’s theory but extended to include a range of other aspects of critical social theory. We finish by suggesting that this approach to the PE scholar—practitioner is even more pertinent due to the field of PE becoming increasingly a third space—something which requires additional research and analysis.